REFLECTION ON THE RELATIONS OF ISLAMIC LAW AND POLITICS - Dio Alif Bawazier; Muhammad Zainuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Discussions about Islamic Law and Politics are always interesting things to discuss. It is interesting because it has become a debate of all time, especially from various circles of formalist madhhab Islamic groups dealing with substantialist schools. The group's debate can be narrowed down to the question of the position of Islamic Law on politics and vice versa. The question is not a simple problem, because the implications are very large for the construction of thought in theory and reality. The purpose of this study is to determine the relationship between power and legal justice, to examine the identity of law and justice, and the necessity of power in law enforcement. The results show that Islamic law is knowledge of human rights and obligations while politics is knowledge of managing public affairs based on power. When viewed from the Islamic law literature, politics is part of the discourse in Islamic law. The Islamic law that regulates politics also has a gap in the interest of incoming power, therefore the Islamic power is obliged to conduct deliberation so that the people's interest is maintained in ijtihadi law and in the application of non-ijtihadi law. Power must uphold justice in every action and its actions cannot be separated from the law. This means that the power to enforce justice is through a just law. Enforcement must be carried out by power so that if power betrays the people, impeachment may be carried out.